VOLATILITAS NILAI TUKAR RUPIAH YANG DIPENGARUHI FAKTOR MONETER INDONESIA DAN AMERIKA SERIKAT - Sunday, Hizkia Juliano; Yuliarmi, Ni Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 13 No 1 (2024): Vol.13.No.1. JANUARI 2024[1-90]DO - 10.24843/EEP.2024.v13.i01.p05, 2024)
The exchange rate plays an important role if a country is going to carry out economic transactions (international trade) with other countries. The economic changes that occurred in Indonesia's economic partner countries quickly affected the Indonesian economy. One of Indonesia's economic partners, namely the United States, whose currency is the dollar is the world's currency, so that changes in United States fundamentals will have an impact on the rupiah exchange rate against the dollar. Bank Indonesia as the central bank in Indonesia always tries to stabilize the rupiah through various policies. A country that has a stable currency value indicates that the country has a stable economic condition. The purpose of this study is to analyze the effect of Indonesian inflation, US inflation, Indonesian interest rates, and US interest rates simultaneously and partially on the Rupiah exchange rate. This research uses a quantitative approach in the form of associative conducted in Indonesia. This study uses monthly data from 2018 - 2021 so that the sample size in this research is 48 observations (observations). The data analysis technique used is panel data regression analysis. The results showed that Indonesia's inflation, US inflation, Indonesian interest rates, and US interest rates simultaneously had a significant effect on the rupiah exchange rate against the dollar. Indonesian inflation has no negative and significant effect on the rupiah exchange rate against the dollar. United States inflation and Indonesian interest rates have a positive and significant effect on the rupiah exchange rate against the dollar. Keywords : inflation, interest rates, exchange rates Klasifikasi JEL: C68, F43, L52